[2+2+2]-cyclotrimerization approach for the synthesis of enantiopure isochromans using a carbohydrate derived dialkyne template - Ramana, C. V.; Suryawanshi, Sharad B. (Tetrahedron Letters, 2008)
An easy access to enantiopure isochromans through cross alkyne trimerization of a glucose derived dialkyne was developed. One of the synthesized isochromans was converted into a novel tricyclic nucleoside by simple transformations. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: isochroman; tricyclic nucleoside; Vorbruggen reaction; Wilkinson's catalyst; [2+2+2]-Cyclotrimerization